Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Siswa pada Materi Invers Matriks di Kelas XI IPA 1 MA Bilingual Batu - Farhadi Farhadi; Ninik Munfarikha (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2020)
This research aims to determine the increment in student learning outcomes on inverse matrix material with Student Teams Achievement Division (STAD) type cooperative learning model. The research subjects were students of class XI IPA 1 MA Bilingual Batu in the 2018/2019 academic year, with a total of 33 students. This type of research is Action Research Classroom (PTK) with the implementation procedure referring to Kemmis and Mc Taggart, which is planning, acting, observing and reflection. This research was conducted in two cycles with the results in the first cycle the average value of the class was 75.4 and in the second cycle the average value of the class was 82.04. From the results obtained, it can be concluded that application of cooperative learning STAD could improve student learning outcomes in the inverse of matrix materials at class XI IPA MA Bilingual Batu.